The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11199-007-9195-3
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Reactions to Masculinity Threat: More Negative Affect Toward Effeminate (but not Masculine) Gay Men

Abstract: We examined whether, due to men's desire to reject stereotypically feminine traits in themselves, a masculinity threat would elicit negative affect toward effeminate, but not masculine gay men. Fifty-three male undergraduates from the United States received bogus feedback that they had either a "masculine" or "feminine" personality before rating affect toward two "types" of gay men: effeminate and masculine. Results were consistent with the notion that defensive reactions target groups stereotyped as having th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
187
3
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(215 citation statements)
references
References 19 publications
13
187
3
8
Order By: Relevance
“…Este prejuicio podría estar ligado con la rigidez de los roles de género, el sentido de la masculinidad y, sobre todo, de la antifeminidad (Parrott, 2009;Parrott y Zeichner, 2008). Algunos hombres heterosexuales perciben a los gays como una amenaza a su masculinidad (Carnaghi, Maass y Fasoli, 2011;Glick, Gangl, Gibb, Klumpner y Weinberg, 2007), ya que asocian la homosexualidad con lo femenino y eso hace que la masculinidad, que consideran inherente en los hombres, pierda fuerza y se vea como difusa (Carnaghi y cols., 2011). Esto a menos que las prácticas homosexuales se sitúen dentro de algún juego (Esterline y Galupo, 2013).…”
Section: Analisis Estadísticosunclassified
“…Este prejuicio podría estar ligado con la rigidez de los roles de género, el sentido de la masculinidad y, sobre todo, de la antifeminidad (Parrott, 2009;Parrott y Zeichner, 2008). Algunos hombres heterosexuales perciben a los gays como una amenaza a su masculinidad (Carnaghi, Maass y Fasoli, 2011;Glick, Gangl, Gibb, Klumpner y Weinberg, 2007), ya que asocian la homosexualidad con lo femenino y eso hace que la masculinidad, que consideran inherente en los hombres, pierda fuerza y se vea como difusa (Carnaghi y cols., 2011). Esto a menos que las prácticas homosexuales se sitúen dentro de algún juego (Esterline y Galupo, 2013).…”
Section: Analisis Estadísticosunclassified
“…This perspective is corroborated by men's concerns about being perceived as gender deviant (McCreary 1994) and evidence that gender transgressions are less tolerated in men than women; for example, boys are significantly more likely than girls to be referred to psychologists for Gender Identity Disorder (Zucker et al 1997). Motivated by fears of being called "pussies" (Berdahl et al 1996) or being labelled homosexual (McCreary 1994), men have been found to reject feminine traits in themselves (Glick et al 2007; see also Vohs et al 2005, Study 2) and others (Schmitt and Branscombe 2001) in order to sustain their social standings (McCreary 1994). In one study, men given false gender deviancy feedback (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown consistent results, which are sometimes interpreted in terms of a conflict between norms of masculinity and men's own dispositions or behavior (Glick, Gangl, Gibb, Klumpner, & Weinberg, 2007;McDermott, Schwartz, Lindley, & Proietti, 2013).…”
mentioning
confidence: 75%